Switzerland's system of free trade agreements: Assessing the impact on imported goods - Philipp Imhof (Aussenwirtschaft, 2021)
In this paper, I estimate the aggregated ex-post effect of Switzerland's free trade agreements on the prospects for imported goods and quantify the implied consumer benefits. Applying a differencein- difference approach to highly disaggregated import data, I find no effects on the quality and variety dimensions but a significant reduction of 8.41% in quality-adjusted prices. Using the share of imports in consumer expenditure, I calculate an average consumer price reduction of 1.43%. The price reduction implies a positive consumer gain. However, I perform a pre-trend test to validate the required parallel trend assumption and document a potential underestimation of the actual effect on consumer gains.
Keywords: F1; F6; 330; Switzerland; free trade agreements; imports